Analisis Kritis terhadap Sosiolinguistik dalam Pendidikan: Sebuah Kajian - Christina Purwanti; I Wayan Rasna; Ida Bagus Putrayasa; Ni Made Rai Wisudariani (Lembaga Pengembangan Kinerja Dosen, 2025)
Sociolinguistics in education is a complex and multidisciplinary field of study that explores the intricate relationship between language, society, and educational processes. It seeks to understand how social factors such as culture, class, ethnicity, and gender influence language use in educational settings, and conversely, how language practices shape social experiences within those contexts. This article aims to conduct a critical analysis of sociolinguistics in education by examining its fundamental concepts, key objects of study, methodological approaches, and the practical benefits it offers to educators and learners alike. Utilizing a critical analysis method, the article investigates how sociolinguistic insights can inform more inclusive, equitable, and effective teaching practices. It also highlights the importance of recognizing language variation and linguistic diversity in classrooms to promote better communication and understanding among students from different social backgrounds. Furthermore, the article underscores that sociolinguistics in education contributes not only to improved pedagogical strategies but also to broader educational policies that value multiculturalism and multilingualism. Ultimately, the study concludes that integrating sociolinguistic perspectives into education can significantly enhance the quality of learning and foster more socially responsive educational environments.